1998
DOI: 10.1002/pro.5560071217
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding and refolding of dimeric creatine kinase equilibrium and kinetic studies

Abstract: Equilibrium and kinetic studies of the guanidine hydrochloride induced unfolding-refolding of dimeric cytoplasmic creatine kinase have been monitored by intrinsic fluorescence, far ultraviolet circular dichroism, and I-anilinonaphthalene-8-sulfonate binding. The GuHCl induced equilibrium-unfolding curve shows two transitions, indicating the presence of at least one stable equilibrium intermediate in GuHCl solutions of moderate concentrations. This intermediate is an inactive monomer with all of the thiol group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 59 publications
6
84
0
Order By: Relevance
“…CK (EC 2.7.3.2) contains multiple cysteine residues and has been widely used as the model system to study enzymatic activity and protein folding. [13][14][15][16][17] Using biochemical and biophysical approaches, we found that the activity and stability of the Fc-III-tagged CK are better than those of the His-tagged CK, and the disulfide linkages in the Fc-III-tagged GFP and CK are different from those in the His-tagged GFP and CK. The results herein provided in-depth understanding of the fusion tag and suggested that the Fc-III tag is a useful tool for the expression and purification of reduced cysteinecontaining proteins.…”
Section: Grant Sponsor: Nsfc; Grant Number: 31270871 (Htd) Grant Smentioning
confidence: 96%
“…CK (EC 2.7.3.2) contains multiple cysteine residues and has been widely used as the model system to study enzymatic activity and protein folding. [13][14][15][16][17] Using biochemical and biophysical approaches, we found that the activity and stability of the Fc-III-tagged CK are better than those of the His-tagged CK, and the disulfide linkages in the Fc-III-tagged GFP and CK are different from those in the His-tagged GFP and CK. The results herein provided in-depth understanding of the fusion tag and suggested that the Fc-III tag is a useful tool for the expression and purification of reduced cysteinecontaining proteins.…”
Section: Grant Sponsor: Nsfc; Grant Number: 31270871 (Htd) Grant Smentioning
confidence: 96%
“…Chemical denaturants, such as guanidine hydrochloride and urea, have been widely used in the investigations of the unfolding of CK (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Because there is a direct interaction between a denaturant and a protein, some thermodynamic parameters may reflect protein-denaturant interaction rather than intrinsic parameters of the protein (15).…”
mentioning
confidence: 99%
“…Synchrotron SAXS combined with the stopped-flow technique can be used to measure the kinetic course of protein unfolding from globular to random coil state, provided unfolding occurs on the second to minute time-scale or longer. In many cases, the backbone secondary structure and the rigid tertiary structure are lost simultaneously during protein unfolding [12]. The SAXS method used in combination with other physicochemical techniques [5] is able to throw light on the interrelation between secondary structure formation and globularization during protein folding.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the value derived from the integrated SAXS intensity, the rate constant obtained from I(0) is identical, while the value from R g is around 2.75-fold lower. This small difference is probably a reflection of the fact that CK unfolding is a complex process [12][13][14]. The different structural parameters derived from the SAXS data may vary in their sensitivity to the different intermediates populated during unfolding.…”
Section: Time-resolved Protein Unfolding Monitored By the Integrated mentioning
confidence: 99%